SEMANGAT KERJA GURU DI SEKOLAH DASAR NEGERI KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Ratna Oktavia (Universitas Negeri Padang, 2014)
This researchaims to determine how the morale of teachers in Public Elementary School District of North Sipora Mentawai Islands. This is a descriptive research. The population in this research is that teachers are civil servants in the Public Elementary School District of North Sipora Mentawai Islands, amounting to 75 people. Technique of sampling stratified proportional random sampling. The amount of sample 45 questionnaire instrument used a Likert scale model sthat have been tested and the results are valid and reliable. Data were analyzed with an average formula. Research results in general morale of teachers in Public Elementary School District of North Sipora Mentawai Islands categorized as high